Investigation on Microstructure and Tensile Fractography of RE Oxides (CeO2/Y2O3) Reinforced AZ91D Magnesium Matrix Composites (Fracture and Structural Integrity, 2022)
The current work aims to investigate the mechanical properties of rare oxide reinforced Mg alloy based MMCs. Magnesium matrix considered in the study is AZ91D alloy, whereas rare earth oxides reinforced were CeO2 and Y2O3. The Y2O3 particulate reinforcement percentage was varied from 1 to 3% in the steps of 1% to study its influence on mechanical properties of MMCs. Stir casting route was adopted to fabricate sample for study. Microstructure analysis illustrated the uniform distribution of particulate in matrix alloys. The obtained results revealed the enhanced mechanical properties such as tensile strength, yield strength, elongation and hardness of MMCs due to increased percentage of reinforcement. Fractography analysis of fracture surfaces demonstrated the microcracks and cleavage were dominant in pure alloy. While particle debonding, extensive plastics deformation were prominent in-addition to microcracks in MMCs.
Keywords: Mechanical Properties; AZ91D; Rare earth oxides; Metal matrix composites